Shaper-assisted full-phase characterization of UV pulses without a spectrometer - Möhring, Jens Markus; Buckup, Tiago; Motzkus, Marcus (Optics letters, 2010)
A full-phase measurement of low-energy femtosecond UV pulses is presented. The method relies on phase retrieval of measured sonogram traces and is greatly simplified by a two-dimensional shaper-assisted cross correlation setup. As all required pulses are generated by the pulse shaper, the method is free of external references and additional tunable filter setups.